Opłaty publiczne jako dodatkowe źródło finansowania ochrony zdrowia w Polsce - Lenio, Paweł (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
The article discusses the matter of introducing public fees as an additional source of financing health care in Poland. In the article general characteristics of the institution of fees in the system of public levies and the model of health care in Poland, including the principles of its financing, were introduced. It was also established whether there is a possibility to introduce a new source of financing in the form of public fees into the Polish health care system, taking legislative solutions functioning in European Union countries and requirements of the provisions of the Constitution of the Republic of Poland into account
Keywords: healthcare; public fees